Optimization formula gastroretentive tablet of ranitidine HCl with floating system - Sulaiman, T.N. Saifullah; Fudholi, Achmad; Nugroho, A. Kharis (INDONESIAN JOURNAL OF PHARMACY, 2011)
Ranitidine  HCl  is  an  H-2  receptor  antagonists  for  the  treatment  of  peptic gastric  secretion  with  a  small  bioavailability,  so  that  should  be  developed  in  a sustained  release  dosage  form  are  retained  in  the  stomach.  Ranitidine  HCl floating  tablet  was  formulation  by  effervescent  system.  Simplex  lattice  design was  applied  to  optimize  the  formula  of  ranitidine  HCl  floating  tablet  by varying levels of Methocel K15M 100-185 mg, sodium bicarbonate 15-100 mg, and  citric  acid0-85 mg.  The  Optimum  formula  determined  by  superimposed contour  plot  from  various  parameters:  flowability  of  granules,  physical properties of tablet and drug release using Design-Expert®program. Based on superimposed  contour  plot obtained  optimum  formula  for  the  area  in  the  range of Methocel K15M 100-145 mg, sodium bicarbonate 20-80 mg and citric acid 25-80 mg.Key words: Ranitidine HCl, Gastroretentive, Simplex lattice design